2022
DOI: 10.3390/met12030449
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Protection of ZK60 Wrought Magnesium Alloys by Micro-Arc Oxidation

Abstract: The influences of the forging process and micro-arc oxidation (MAO) coating on the corrosion behavior of ZK60 wrought magnesium alloys exposed to salt spray and constant stress corrosion conditions were investigated. The microstructure of the ZK60 Mg alloy specimens forged under different temperatures (i.e., 250, 300, and 450 °C) was characterized using metallography, EBSD, and SEM. It was demonstrated that the ZK60 alloy forged at 300 °C (i.e., ZK60EF-300) had finer grain and uniformly distributed β-phase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
3
4
0
Order By: Relevance
“…It is observed that the corresponding value for the studied alloy is higher than that of the commercial ZK 60 alloy. For the commercial ZK 60 alloy, the corrosion rate, already reported in other experimental works, is similar to that obtained in this present work [ 65 , 66 , 67 , 68 , 69 , 70 ]. Despite the difference, it can be said that both materials have a similar trend as they are within the same order of magnitude.…”
Section: Resultssupporting
confidence: 92%
“…It is observed that the corresponding value for the studied alloy is higher than that of the commercial ZK 60 alloy. For the commercial ZK 60 alloy, the corrosion rate, already reported in other experimental works, is similar to that obtained in this present work [ 65 , 66 , 67 , 68 , 69 , 70 ]. Despite the difference, it can be said that both materials have a similar trend as they are within the same order of magnitude.…”
Section: Resultssupporting
confidence: 92%
“…A similarity in the corrosion parameters' evolution can be seen for both neutral and acidic pH. If we compare these values with those corresponding to the commercial ZK60 alloy (around 1.45 mm/year [63][64][65][66][67][68]), it can be found that the values obtained here can be considered quite satisfactory.…”
Section: Corrosion Analysis Of the Pbf-lb/m-processed Mg-based Alloysupporting
confidence: 62%
“…However, as a good result noted from these experiments, it should be mentioned and emphasized that at a neutral pH, the corrosion rate of the Mg-10Zn-0.8Ca-0.5Zr alloy (1.426 mm/year) is very close to that of the alloy considered an etalon for comparison with nowadays -ZK 60 (1.45 mm/year) [63][64][65][66][67][68].…”
Section: Corrosion Analysis Of the Pbf-lb/m-processed Mg-based Alloysupporting
confidence: 55%
“…In the MAO process, a stainless steel cylindrical container serves as the cathode and a magnesium alloy functions as the anode. In the early stage of MAO, a thin and dense layer was formed on the surface of the magnesium alloy (Xue et al , 2022). Then porous and microcracks start to present on the former layer, making the MAO coating exhibit a double-layer structure.…”
Section: Corrosion Protection Of Friction Stir-welded Magnesium Alloysmentioning
confidence: 99%